IMPACT OF THE COVID-19 PANDEMIC PROBLEM ON ASSOCIATE EDUCATION - Akpınar, Esra; Akpınar, Burhan (Hatay Mustafa Kemal University, 2021)
This study aims at analyzing reflections of the COVID-19 pandemic on associate education. Conducted in the document analysis model, this study revealed the following results. The COVID-19 pandemic, which appeared in 2019, led to a serious trauma at all the educational levels. Triggering learning voids in education, the trauma was felt more deeply in the Vocational Schools of the associate education due to two main reasons. The first reason was the short educational period of these schools which consisted two years while the second reason was their practice-oriented educational policy. Due to the short educational period, it is uncertain when and how the face-to-face education in the Vocational Schools, which was interrupted partly or completely during the pandemic process, will be compensated for. The negative impacts of the learning voids and particularly deficiencies deriving from practical skills, which appeared during the pandemic process, on the labor market are inevitable. Therefore, it is imperative that along with actions to be taken, short-, medium- and long-term plans for the Vocational Schools students of the pandemic period have to be made urgently. In the short-term, plan requires enforcing a practice-oriented make-up term in the summer semester of 2021. The medium-term plan is the requirement of an induction, orientation training for the Vocational Schools graduates of the pandemic period. The long-term plan, however, is the suggestion of the Hybrid Vocational School Model which means blending face-to-face education with virtual and digital technology-based education. As a matter of fact, it is observed that steps have been taken towards this during the 2021-2022 education period. As a prerequisite of the Information Age, the hybrid model is essential to prepare the Vocational Schools for crisis like pandemics in the future.

Bu çalışmanın amacı, Covit-19 pandemisinin ön lisans eğitimine yansımalarını analiz etmektir. Çalışma, dokümanter analiz modelinde yürütülmüş ve aşağıdaki sonuçlara ulaşılmıştır. 2019 yılında ortaya çıkan Covit-19 pandemisi, bütün eğitim kademelerinde ciddi bir sarsıntıya yol açmıştır. Eğitimde öğrenme boşluklarına yol açan bu sarsıntı, iki nedenden dolayı ön lisans kademesindeki Meslek Yüksekokullarında daha derinden hissedilmiştir. Birincisi, bu okulların iki yıl şeklindeki kısa eğitim süresi, ikincisi ise, uygulama ağırlıklı eğitim politikasıdır. Kısa eğitim süresinden dolayı, pandemi sürecinde meslek yüksekokullarında kısmen veya tamamen kesintiye uğrayan yüz yüze eğitimin nasıl ve ne zaman telafi edileceği belirsizdir. Pandemi döneminde oluşan öğrenme boşluklarının ve özellikle de uygulamaya dair pratik becerilerle ilgili eksikliklerin, iş piyasasına olumsuz yansımaları kaçınılmazdır. Dolayısıyla pandemi kuşağı meslek yüksekokulu öğrencilerine yönelik kısa, orta ve uzun vadeli önlem ve planların ivedilikte yapılması zorunludur. Kısa vadeli plan, kısa vadede yaz mevsimlerinde ek bir uygulama ağırlıklı telafi dönemi ihdas edilmesidir. Orta vadeli plan, pandemi kuşağı meslek yüksekokulu mezunlarına işbaşı oryantasyon eğitiminin zorunlu kılınmasıdır. Uzun vadeli plan ise, yüz yüze eğitim ile sanal ve dijital teknoloji tabanlı eğitimin harmanlamasını ifade eden Hibrit meslek yüksekokulu modeli önerisi şeklindedir. Nitekim 2021-2022 eğitim döneminde buna yönelik adımların atılmış olduğu gözlenmektedir. Bilgi Çağı’nın gereği olan hibrit model meslek yüksekokullarını gelecekte pandemi benzeri krizlere hazırlamak bakımından önemlidir.
COVID-19 PANDEMİ SORUNUNUN ÖN LİSANS EĞİTİMİNE YANSIMALARI